# 5y 2y 5 0

5y 2y 5 0

## Simple and all-time practice solution for 5y(2y-5)=0 equation. Check how easy it is, and learn it for the hereafter. Our solution is simple, and like shooting fish in a barrel to sympathise, so don`t hesitate to utilize it as a solution of your homework.

If information technology’s not what You are looking for blazon in the equation solver your own equation and let us solve it.

## Solution for 5y(2y-5)=0 equation:

```Simplifying 5y(2y + -v) = 0  Reorder the terms: 5y(-v + 2y) = 0 (-five * 5y + 2y * 5y) = 0 (-25y + 10y2) = 0  Solving -25y + 10ytwo
= 0  Solving for variable 'y'.  Factor out the Greatest Common Cistron (GCF), '5y'. 5y(-5 + 2y) = 0  Ignore the cistron 5.
Subproblem 1Set the factor 'y' equal to zero and attempt to solve:  Simplifying y = 0  Solving y = 0  Move all terms containing y to the left, all other terms to the right.  Simplifying y = 0
Subproblem 2Set the factor '(-5 + 2y)' equal to cipher and endeavor to solve:  Simplifying -5 + 2y = 0  Solving -5 + 2y = 0  Move all terms containing y to the left, all other terms to the right.  Add together '5' to each side of the equation. -five + 5 + 2y = 0 + five  Combine like terms: -5 + v = 0 0 + 2y = 0 + 5 2y = 0 + five  Combine like terms: 0 + 5 = 5 2y = 5  Divide each side by '2'. y = ii.five  Simplifying y = two.5Solutiony = {0, 2.5}```